2008
DOI: 10.1021/jp806939q
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry between Absorption and Photoluminescence Line Shapes of TPD: Spectroscopic Fingerprint of the Twisted Biphenyl Core

Abstract: We analyze absorption, photoluminescence (PL), and resonant Raman spectra of N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), with the aim of providing a microscopic interpretation of a significant Stokes shift of about 0.5 eV that makes this material suitable for stimulated emission. The optical spectra were measured for TPD dissolved in toluene and chloroform, as well as for polystyrene films doped with varying amounts of TPD. In addition, we measured preresonant and resonant Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 46 publications
7
33
0
1
Order By: Relevance
“…On the other hand, in other materials, such as TPD, both absorption and PL spectra remain unchanged with concentration. Recent calculations based on density functional theory, together with resonant Raman spectroscopy, have been used to propose a model to explain this behavior [44]. Results have shown that the influence of molecular interactions is much smaller than that of the torsional modes of TPD at very low frequency.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in other materials, such as TPD, both absorption and PL spectra remain unchanged with concentration. Recent calculations based on density functional theory, together with resonant Raman spectroscopy, have been used to propose a model to explain this behavior [44]. Results have shown that the influence of molecular interactions is much smaller than that of the torsional modes of TPD at very low frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The inner reorganization energies k play a crucial role in the interpretation of the Stokes shift [13,14]. The total reorganization energies of the three compounds are 0.566 eV, 0.714 eV and 0.861 eV respectively (Table 4).…”
Section: Vibrational Frequencies and Model Pl Spectramentioning
confidence: 99%
“…The elongation of high-frequency modes contribute to the higher first vibronic peak in PL spectra and the elongation of lowfrequency modes results in a broadening of the vibronic subbands defined by the high-frequency modes [13][14][15][16]. Relative small number of low-frequency modes would bring out a distinct energy level system between two energy levels which root in the main peak and the shoulder peak.…”
Section: Resonant Raman Spectra and Vibrational Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…We use two kinds of relaxed excited geometries: First, the result of the TD-DFT geometry optimization, and second, a modified excited geometry where changes of the twisting angle of each phenyl group around the bond connecting it to the tetracene core are eliminated. From similar investigations on other molecules containing phenyl groups we expect that this procedure minimizes artifacts arising from finite angle effects related to the relatively large changes of these angles in the relaxed excited geometry [25].…”
Section: B Dft Calculationsmentioning
confidence: 99%